Análisis Multitemporal y de Fragmentación de la Cobertura de Bosque en el Municipio de San Jacinto, Bolívar (2022)
In this work, was made an identification of the coverage present in the Municipality of San Jacinto, Bolívar’s Department, supported by two Sentinel 2 satellite images from the years 2015 and 2022, through supervised classification and a fragmentation analysis. An analysis of changes in the forest cover that have occurred in the municipality was carried out, mainly after the signing of the peace agreement in Colombia, in addition to correctly identifying the covers that present greater susceptibility to anthropic intervention. Finding that for the year 2015 the natural covers occupied 54.29% of the total area of the municipality, while for the year 2022 this occupation decreased representing 43.48% of the municipality, which indicates that although the natural and semi-natural covers presenting high representativeness in the municipality, the forest cover contributes little percentage of area to the total with 3.3%. The municipality has had many changes in recent years, mainly identifying the loss of natural and semi-natural coverage in important magnitudes. For example, the forest cover decreased by 2,054.48 hectares during the analysis period, especially due to the increase in agricultural activities in the municipality. On the other hand, in the fragmentation analysis, the core area index (CAI) was identified for the year 2015 and 2022, where it was found that the secondary vegetation has a higher value (61.8) for 2015; while the coverage of shrublands is the one with the highest value (76.45) in the analysis of the year 2022.